The Essence and Principles of Building a Business Model of Adult Education Institutions - Zelenin Yuriy M. (Bìznes Inform, 2018)
The article considers approaches to definition of essence of business model by leading experts of science. On the basis of the complex theoretical-methodological research concerning content of the concept of «business model», the author substantiates expediency of applying to the process of formation of business models of adult education principles of dynamics, competence, universality, and innovation. According to the allocated principles, the definitions of the term of «business model» are systematized. The interrelation of the basic elements of business model is analyzed with attention to the key principles. As a result of the critical analysis of polysemy of the concept of «business model of organization», the main advantages and disadvantages of the existing scientific definitions are defined and generalized. The author clarifies that, when interpreting the essence of the business model of organization, it is advisable to focus on polyfunctionality and on multi-vector nature of the indicated term. It is substantiated that adult education institutions are oriented towards working-out of a quality educational product as indisputable value for the key consumers, i.e. top managers. It has been determined that an efficient business model is the key to successful implementation of all processes in the internal and external environment of organization. The author’s own definition of the concept of «business model of adult education institution» is proposed.